Kenaf: A Multi-Purpose Crop for Several Industrial Applications [electronic resource] : New insights from the Biokenaf Project - Monti, Andrea; Alexopoulou, Efthimia; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Natural plant fibers fibres are being increasingly used in manufacturing industrial products because of their renewable and biodegradable natures. Kenaf is an annual bast fibre crop that can provide fibres for several industrial applications (composites, insulation mats, absorbents, bedding material, etc.) as well as raw material for energy exploitation (solid biofuels). Kenaf: A Multi-Purpose Crop for Several Industrial Applications introduces the physiology and field management of kenaf, agronomy, productivity, harvesting as well as its the industrial and energy uses of this promising non-food crop. {u026E}cluding recent research collected by the BIOKENAF project, Kenaf: A Multi-Purpose Crop for Several Industrial Applications provides a global picture of state of the art research and developments with Kenaf from Asia, USA and Australia. This thorough introduction if followed up with an assessment of the crops economic viability as well as an the environmental impact assessment of kenaf. lthough not a new crop, Kenaf: A Multi-Purpose Crop for Several Industrial Applications provides a comprehensive introduction to this crop and its developing applications for energy engineers, industry managers, politicians and managers working to develop sustainable energy sources and bio-economies.
Preface -- Foreword -- 1.Origin, Description, Importance and Cultivation Area of Kenaf -- 2.Crop Physiology -- 3.The Breeding of Kenaf -- 4.Crop Management -- 5.Environmental aspects of kenaf production and use -- 6.Kenaf Fibre Crop for Bio-Economic Industrial Development -- 7.Economic and Financial Analysis: The farmer?s point of view.
Keywords: Energy; Renewable energy resources; Energy harvesting